Flexible bronchoscopic removal of a three piece foreign body from a child's bronchus - Mehta, D (Australasian Medical Journal, 2012)
Foreign body aspiration can be a life-threatening event especially in young children because they have smaller diameters of airway lumen, moreover, the delay in the diagnosis and subsequent therapeutic intervention can further increase the risk of morbidity.(1, 2) A retained foreign body can result in inflammatory response and granulation tissue formation around the object which make the foreign body removal difficult.(3) In such situations surgical intervention is usually needed but with interventional pulmonology modalities we can restrict the need for surgery.(4) Rigid bronchoscopy under general anaesthesia is the gold standard of diagnosis and management of foreign body aspiration.(1) However, nowadays flexible bronchoscopy is more widely available and most pulmonary physicians are trained in its use so it can be used to remove such foreign bodies. We hereby report a case of a neglected foreign body which remained in the bronchus of a child for 11 days, successfully removed by flexible bronchoscopy.